2023
DOI: 10.1093/gbe/evad068
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transposon Transfer and Their Ecological Drivers: The Case of Flower-breeding Drosophila

Abstract: Understanding the mechanisms that shape the architecture, diversity and adaptations of genomes and their ecological and genetic interfaces is of utmost importance to understand biological evolution. Transposable elements (TEs) play an important role in genome evolution, due to their ability to transpose within and between genomes, providing sites of non-allelic recombination. Here we investigate patterns and processes of TE driven genome evolution associated with niche diversification. Specifically, we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Since the discovery of horizontally transmitted P-elements in Drosophila species, a wealth of studies have reported the exchange of transposable elements between non-hybridizing insect species 5,12,34 . The piRNA pathway has been proposed to coordinate an adaptive defense mechanism against newly invading transposons 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of horizontally transmitted P-elements in Drosophila species, a wealth of studies have reported the exchange of transposable elements between non-hybridizing insect species 5,12,34 . The piRNA pathway has been proposed to coordinate an adaptive defense mechanism against newly invading transposons 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal transposon transfer (HTT) is the phenomenon in which a given TE “jumps” to the genome of a non-closely related species, i.e., sexually isolated organisms ( Panaud, 2016 ). The role of HTT in shaping diversity as an endogenous source of evolution is widely recognized ( Pace et al, 2008 ; Gilbert and Feschotte, 2018 ; Carvalho et al, 2023 ), and its frequency is much higher than previously thought ( Schaack et al, 2010 ; Panaud, 2016 ; Peccoud et al, 2017 ; Melo and Wallau, 2020 ).…”
Section: Introductionmentioning
confidence: 99%